Kawista fruit improves lung histopathology of rats exposed to cigarette smoke - Raharja, Kristian Triatmaja; Susilawati, Endang Fauziyah; Romadhoni, Ita Fatkhur (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Free radicals in cigarettes can increase oxidative stress, exacerbating inflammation and activating alveolar macrophage cells. The phenolic components of kawista fruit act as antioxidants that reduce free radicals.Objective: To determine the effect of kawista fruit on alveolar macrophage activation in Wistar rats exposed to cigarette smoke (CS).Methods: The experimental research used a post-test only group design with a completely randomized design for 35 days. Wistar 25 male rats were divided into five groups: positive control (exposed to cigarette smoke), negative control (no treatment), O1, O2, and O3 (exposed to cigarette smoke and Kawista fruit sonde at doses O1=0,5, O2=0,6, and O3=0,7 g/kg BW). Data were analyzed using ANOVA one analysis of variance and LSD test.Results: Kawista fruit given preventively at doses of 0,6 and 0,7 g/kg BW could prevent the activation of lung alveolar macrophages in rats exposed to cigarette smoke (p=0,000). The lowest number of alveolar macrophages was seen at a dose of 0,7 g/kg BW.Conclusion:  Kawista fruit inhibited the increase in the number of alveolar macrophages and improved the lung histopathology of Wistar rats exposed to cigarette smoke.